Exfoliation of 2D materials by high shear mixing - Coleman, Jonathan; Mc Evoy, Niall (My University, 2019)
While it has been demonstrated that large scale liquid exfoliation of graphene is possible using high-shear exfoliation, it has not yet been shown to be applicable to a broader range of layered materials. In addition, it would be useful to determine whether the mechanisms reported for shear exfoliation of graphene also apply to other 2D materials. In this work we show that previous models describing high-shear exfoliation of graphene apply to MoS2 and WS2. However, we find the minimum shear rate required to exfoliate MoS2 and WS2 to be ∼3 × 104 s-1, somewhat higher than the value for graphene. We also demonstrate the scalability of shear exfoliation of WS2. By measuring and then optimising the scaling parameters, shear exfoliation of WS2 is shown to be capable of reaching concentrations of 1.82 g l-1 in 6 h and demonstrating a maximum production rate of 0.95 g h-1.
PUBLISHED
cited By 0
Keywords: graphenescale upshear mixerTMD'sWS2; graphenescale upshear mixerTMD'sWS2